Pengaruh Motivasi Prestasi, Kekuasaan, Dan Afiliasi Terhadap Kinerja Dosen Pada Perguruan Tinggi Swasta Di Surakarta - Kusasih, Ida Ayu Kade R.; Mutmainah, Hestin; Ardyan, Elia (STIE Surakarta, 2014)
Lecturers are professional educators and scientists with the main task of transforming, developing, and disseminating science, technology, and arts through education, research, and community service. The purpose of this study is to determine how much influence achievement motivation, power motivation, and affiliation motivation on the performance of lecturers, especially female lecturers at private universities in Surakarta which certainly has her own characteristics and challenges in performing her dual role. When the motivations of a lecturer are known, it can be used as the basis of giving motivation to improve her performance.